Aplicación de la metodología tpm para el mejoramiento de la fiabilidad de los equipos industriales en el área de producción de puertas económicas en la empresa Induce del Ecuador - Cerón Cerón, Víctor Javier (2022)
Lack knowledge and organization in a master maintenance plan for the industrial equipment of the company INDUCE DEL ECUADOR has caused unexpected stoppages affecting the continuity of production of economic doors that in a quarterly OEE average is 60% being unacceptable producing significant economic losses. Maintenance is a service that combines a set of activities, industrial equipment must be in good condition providing safe conditions for personnel working in the company. Total Productive Maintenance (TPM) is a management system that prevents and minimizes losses and maximizes efficiency throughout the life of your production system and involves all employees from all departments of the company. A TPM can make its organization stand out from the competition, reduce costs, improve response times and impact reliability in industrial equipment, operator knowledge and product quality. TPM methodology has been applied on INDUCE DEL ECUADOR company at production area of economic doors, developing a total maintenance plan for the industrial equipment that are part of production line such as: hydraulic press, hydraulic cutter, hydraulic bender, die cutter, Mig welder and compressor. The value of the OEE indicator was determined, which allows to know the efficiency of production area of current state company and later when TPM methodology is applied. Also establishing costs of losses that currently generates the company for not having a maintenance plan and gains that will be obtained with TPM. Subsequently to involve total maintenance plan in the company INDUCE DEL ECUADOR it was made a proposal for a software technology using Excel tool that will help to have a continuous monitoring of machines, helping to monitor what type of maintenance should be performed, their tools, responsible, duration time, critical spare parts and whether or not the maintenance was executed.